Faktor-Faktor Yang Berhubungan Dengan Sikap Siswi Di SMA PGII 1 Bandung Dalam Menjaga Kebersihan Alat Reproduksi Bagian Luar - Elizabeth Ari; Astri Nur Raharjo (Jurnal Medika Cendikia, 2014)
Reproductive health is physical health, mental, and social well-being associated with the systems and functions, as well as the reproduction process and not just a condition that is free of disease or disability. Reproductive received less attention in everyday life, this is caused by our culture that sometimes feel uncomfortable to talk about sexual issues purpose of this study to know the relationship between personal experience, the influence of other people who are considered important, culture, mass media, and emotional factors with a high school student attitude PGII 1 Bandung in maintaining the cleanliness of the outside of the reproductive organs. Research Methods: Quantitative methods and analytic correlational design with cross sectional pendeketan, using Chi Square test data analysis. Data collection instrument using a questionnaire with 39 closed questions. The number of samples taken 196 female students with simple random sampling. The study states that there is no relationship between personal experience factor (p-value 0.762), the influence of other factors that are considered important (p-value 0.406), cultural factors (p-value 0.755), mass media factor (p-value 1, 00), and emotional factors in student attitude (p-value 0.762). Recommendations from this study continue to hold a school health education on reproductive health are continuous and scheduled Keywords : reproductive health, adolescent, attitude